2008
DOI: 10.1128/jvi.00410-08
|View full text |Cite
|
Sign up to set email alerts
|

Primate Lentivirus Capsid Sensitivity to TRIM5 Proteins

Abstract: Mammalian cells express several factors that inhibit lentiviral infection and that have been under strong selective pressure. One of these factors, TRIM5, targets the capsid protein of incoming retrovirus particles and inhibits subsequent steps of the replication cycle. By substituting human immunodeficiency virus type 1 capsid, we were able to show that a set of divergent primate lentivirus capsids was generally not susceptible to restriction by TRIM5 proteins from higher primates. TRIM5␣ proteins from other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 34 publications
4
58
0
Order By: Relevance
“…We have shown previously that ancestral TRIM5␣ restricted HIV-1 better than did the hominoid TRIM5␣ ancestor and human TRIM5␣ (13). Likewise, SIV strains in hominoids and Old World monkeys are resistant to host TRIM5␣ but sensitive to other simian TRIM5␣ proteins in a species-specific manner (15,25,54). In New World monkeys, TRIM5␣ mediates species-specific restriction against foamy viruses naturally found in those species (39).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that ancestral TRIM5␣ restricted HIV-1 better than did the hominoid TRIM5␣ ancestor and human TRIM5␣ (13). Likewise, SIV strains in hominoids and Old World monkeys are resistant to host TRIM5␣ but sensitive to other simian TRIM5␣ proteins in a species-specific manner (15,25,54). In New World monkeys, TRIM5␣ mediates species-specific restriction against foamy viruses naturally found in those species (39).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this species specificity, Vpu was not predicted to support HIV-1 replication in macaques. Indeed, HIV-1 is unable to replicate in macaques, not only because of a BST-2 restriction but also because of restrictions imposed by APOBEC3G and Trim5␣ (72,73). Nevertheless, the macaque system has gained importance for HIV research and is currently the most widely used nonhuman primate model for vaccine development and the study of host immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Human TRIM5a inhibits some retroviruses, such as the equine infectious anemia virus (EIAV) and the so-called 'N strains' of the murine leukemia virus (N-MLV) 4,5,10,11 but it only weakly restricts HIV-1, HIV-2 and many simian immunodeficiency viruses (SIVs), including SIVs from macaques (SIV mac ), from African green monkeys (SIV AGM ) and from chimpanzees (SIV cpz ). 5,12,13 It is likely that the limited restriction range of TRIM5a hu has made it possible for lentiviruses infecting nonhuman primates to cross-species and thrive in humans, thus causing the current HIV pandemic. It has been suggested that TRIM5a hu derives from an ancestor gene that had evolved to provide resistance against unknown, now-extinct retroviruses, leaving us more vulnerable to infections by modern simian lentiviruses.…”
Section: Introductionmentioning
confidence: 99%